Effect of Mobile Phone Usage on Students during the Pandemics Covid-19 (Global Journal of Human-Social Science, 2022)
Our aim was to know the effect of mobile phone during lockdown among students A total number of 108 students completed the questionnaire The questions were asked related to mobile phone usage Students of secondary Higher secondary and higher education were the sample of the study Online survey was conducted finding of the study showed that all students in the study were using mobile phone majority of students were using their mobile phone more than before the lockdown During the pandemic they are spending more time on their mobile phone for different purposes like studies entertainment for gaming etc Result of the study also revealed that students are facing problem like eye irritation neck pain etc
Keywords: mobile phone; usage; pandemics covid-19; students (secondary; higher secondary and higher education)